The Contradictory Role of Corruption in Corporate Innovation Strategies - James Okrah; Alexander Nepp (Foresight and STI Governance)
This study considers the influence of the work experience of Russian top managers on the willingness to stimulate innovative processes in companies, including using at a certain stage some corruption schemes to bypass bureaucratic barriers.Using a logit model based on enterprise surveys carried out by the World Bank, data on managers of small and medium-sized businesses were analyzed.It was revealed that the presence of "corruption competencies" has a positive effect on the innovative activity of enterprises in developing countries. This effect is due to the fact that corruption in such countries acts as a mechanism to reduce transaction costs associated with innovation. The level of corrupt activity of managers increases as they accumulate experience due to the high degree of bureaucratization and the weakness of institutions, which turn into time and financial costs for enterprises. In the short term, corruption can accelerate the development of innovation, but cannot serve as a permanent tool in this regard, since its long-term consequences turn out to be extremely negative.